“The weight of my skeleton is my only honesty” : language and the speaking body in Marlene van Niekerk’s Agaat - Levinrad, Ester (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (English))--University of Stellenbosch, 2010.